Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.4162/nrp.2017.11.3.232
|View full text |Cite|
|
Sign up to set email alerts
|

Instant noodle consumption is associated with cardiometabolic risk factors among college students in Seoul

Abstract: BACKGROUND/OBJECTIVESIncreased consumption of instant noodles has recently been reported to be positively associated with obesity and cardiometabolic syndrome in South Korea, which has the highest per capita instant noodle consumption worldwide. This study aimed to investigate the association between instant noodle consumption and cardiometabolic risk factors among college students in Seoul.SUBJECTS/METHODSThe study subjects consisted of 3,397 college students (1,782 male; 1,615 female) aged 18-29 years who pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
1
24
1
4
Order By: Relevance
“…Several studies explain that the excessive consumption of highly processed products and sugary drinks, plus a sedentary lifestyle (Ross et al, 2000;Swift et al, 2014;Romieu et al, 2017), are detonators of overweight, obesity, and diabetes (Taylor and Jacobson, 2016). In particular, the consumption of instant soups has been related to the increase of cardiovascular diseases (Shin et al, 2014;Huh et al, 2017). We provide further evidence on the existing correlation between the prevalence of certain health conditions (diabetes, obesity, and overweight) and the rate of land-use change, biodiversity conservation, and modification of dietary patterns, in countries such as China, India, Italy, and Mexico over the past 40 years (Ley et al, 2014;WHO, 2016).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies explain that the excessive consumption of highly processed products and sugary drinks, plus a sedentary lifestyle (Ross et al, 2000;Swift et al, 2014;Romieu et al, 2017), are detonators of overweight, obesity, and diabetes (Taylor and Jacobson, 2016). In particular, the consumption of instant soups has been related to the increase of cardiovascular diseases (Shin et al, 2014;Huh et al, 2017). We provide further evidence on the existing correlation between the prevalence of certain health conditions (diabetes, obesity, and overweight) and the rate of land-use change, biodiversity conservation, and modification of dietary patterns, in countries such as China, India, Italy, and Mexico over the past 40 years (Ley et al, 2014;WHO, 2016).…”
Section: Discussionmentioning
confidence: 74%
“…As a result, in the last 40 years, a crescent association has been developing between the production of sugars (sucrose and fructose), land-use change for agricultural activities, and the increase of blood sugar, obesity, and overweight (Vega et al, 2018); moreover, several studies found a strong association between the consumption of sugary drinks and the incidence of type-2 diabetes (Gross et al, 2004;Bomback et al, 2010;Malik et al, 2010). From this data, it is clear that dietary consumption patterns influence the incidence of NCD (specifically cardiometabolic diseases; Shin et al, 2014;Huh et al, 2017), as well as agricultural production systems, which in turn negatively affect the environment by being associated with the consumption of fossil fuels, greenhouse gas emissions, and temperature rising.…”
Section: Introductionmentioning
confidence: 97%
“…According to Huh et al [48], frequent consumers of instant noodles, high-fat and processed meats, sweets and confectionery and carbonated beverages had higher plasma triglyceride levels, diastolic blood pressure, and fasting blood glucose levels than the infrequent consumers. The overall diet exceeded WHO upper limits for fat, saturated fat, free sugars and Na density, with less fibre than recommended.…”
Section: Effect Of Convenience Foods On the Healthmentioning
confidence: 99%
“…A study had also reported a positive association between anthropometric and higher consumption of ultra-processed instant foods, contributing to long-term obesity [20]. A study cited that plasma triglyceride levels and blood glucose levels were higher among frequent consumers of instant foods such as noodles, sweets, beverages than infrequent consumers [21].…”
Section: Attributes Affecting the Purchase And Consumption Of Convenimentioning
confidence: 99%